2007
DOI: 10.1152/ajpcell.00406.2007
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the selectivity filter of a TRPV channel: rapid accessibility of contiguous residues from the external medium

Abstract: The transient receptor potential type V5 (TRPV5) channel is a six-transmembrane domain ion channel that is highly selective to Ca 2ϩ . To study the topology of the selectivity filter using the substituted cysteine accessibility method (SCAM), cysteine mutants at positions 541-547 were studied as heterotetramers using dimeric constructs that couple the control channel in tandem with a cysteine-bearing subunit. Whole cell currents of dimeric constructs D542C, G543C, P544C, A545C, and Y547C were rapidly inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Similar observations have been made with the calcium impermeable TRPM4 channel, in which mutations in the putative selectivity filter enabled calcium permeation through the receptor [182]. The outer pores of the TRPV6 and TRPV5 have been probed by using the substituted cysteine accessibility method (SCAM), and the results are also consistent with a pore topology similar to Kv channels [181,183,184], albeit with differences regarding the size of the pore and the nature of the selectivity filter. Interestingly, a recent study suggests that the TRPV1 exhibits a phenomenon previously observed in P2X receptors [185,186] called pore dilation, in which the channel's selectivity for large cations is increased as compared to sodium ions in an agonist exposure-time-and concentration-dependent manner [187].…”
Section: The Pore and The Activation Gate Of The Trpv1 Channelsupporting
confidence: 63%
“…Similar observations have been made with the calcium impermeable TRPM4 channel, in which mutations in the putative selectivity filter enabled calcium permeation through the receptor [182]. The outer pores of the TRPV6 and TRPV5 have been probed by using the substituted cysteine accessibility method (SCAM), and the results are also consistent with a pore topology similar to Kv channels [181,183,184], albeit with differences regarding the size of the pore and the nature of the selectivity filter. Interestingly, a recent study suggests that the TRPV1 exhibits a phenomenon previously observed in P2X receptors [185,186] called pore dilation, in which the channel's selectivity for large cations is increased as compared to sodium ions in an agonist exposure-time-and concentration-dependent manner [187].…”
Section: The Pore and The Activation Gate Of The Trpv1 Channelsupporting
confidence: 63%
“…First, the molecular surface representation shows the localization and orientation of the D542 residue as a negatively charged ring at the entry of the channel (Fig. S2B)1126. Interestingly, the inner pore region contains the tryptophan residue (W583) residue at the intracellular end of TM6, with its side chain pointing towards the ion permeation pathway (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since its introduction by Koshland and co-workers [4], site-directed thiol chemistry has been exploited in many ways, such as to identify the residues that line the pathway taken by solutes across a membrane pore [5,37,38] and the amino acids forming the charge and solute specificity filters as well as the widths of these filters in such pores [5,39]; to monitor the binding of substrates to enzymes and transporters and the ensuing conformational changes; to study the topology of membrane proteins in different physiological states, for instance in different lipid environments [40]; to identify the residues involved in protein-protein interactions [41]; and to follow the transit of the passenger domain through the C-terminal β barrel of bacterial autotransporters [3]. Since its introduction by Koshland and co-workers [4], site-directed thiol chemistry has been exploited in many ways, such as to identify the residues that line the pathway taken by solutes across a membrane pore [5,37,38] and the amino acids forming the charge and solute specificity filters as well as the widths of these filters in such pores [5,39]; to monitor the binding of substrates to enzymes and transporters and the ensuing conformational changes; to study the topology of membrane proteins in different physiological states, for instance in different lipid environments [40]; to identify the residues involved in protein-protein interactions [41]; and to follow the transit of the passenger domain through the C-terminal β barrel of bacterial autotransporters [3].…”
Section: Scam Tmmentioning
confidence: 99%